Existence of Solutions for a Class of Quasilinear Elliptic Systems with Indefinite Weights (Journal of Partial Differential Equations, 2005)
By use of the fibering method introduced by Pohozaev S I, the existence of positive solutions for homogeneous Dirichlet problem of a class of quasilinear elliptic systems with indefinite weights is obtained.
Keywords: Fibering method; Quasilinear elliptic systems; Indefinite weights